Zn / Co-MOFs / PVDF (Polyvinylidene Fluoride) mixed matrix membrane as well as preparation method and application thereof
By introducing Zn/Co-MOFs/PVDF mixed matrix membrane and advanced oxidation technology into membrane separation technology, the problem of low removal efficiency of emerging antibiotic pollutants in the existing technology is solved, and efficient and environmentally friendly pollutant removal effect is achieved.
Patent Information
- Application Number
- CN202510042169.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-22
AI Technical Summary
When the existing membrane separation technology removes emerging antibiotic pollutants in water, there is a restrictive effect between poor anti-pollution performance, permeability and selectivity of the membrane, resulting in low separation efficiency and it is difficult for a single membrane technology to completely remove pollutants.
Zn/Co-MOFs/PVDF mixed matrix membrane was used to prepare Zn/Co-MOFs nanomaterials by hydrothermal method, and introduced them into the cast film liquid by non-solvent phase separation method (NIPS). Combined with advanced oxidation technology, it can effectively remove emerging antibiotic pollutants.
The permeability and separation efficiency of the membrane are improved, the removal rate of emerging antibiotic pollutants reaches 99.37%, and the cost of industrial wastewater treatment is reduced, and the process is green and environmentally friendly.
Smart Images

Figure CN119857377A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of separation membrane materials, and in particular to a Zn / Co-MOFs / PVDF mixed matrix membrane and a preparation method and application thereof. Background Art
[0002] Emerging pollutants refer to toxic and hazardous chemicals with characteristics such as environmental persistence, biological toxicity and bioaccumulation. With the acceleration of global industrialization, the large increase in emerging antibiotic pollutants in water bodies has become an environmental issue of increasing concern. Tetracycline is currently the most widely used emerging antibiotic pollutant in the world, with the characteristics of small size, long half-life, and difficulty in degradation. As a new type of water treatment technology, membrane separation technology has shown great potential in the field of water treatment due to its advantages such as simple operation, high efficiency, and easy modularization. However, traditional membrane separation technology has defects such as poor membrane anti-pollution performance and the restriction effect between permeability and selectivity, which affect the separation efficiency of the membrane, and a single membrane technology cannot completely remove pollutants, limiting the application prospects of membrane separation technology. For example, commercial ultrafiltration membranes cannot remove antibiotic pollutants in water by pore size screening, and the removal rate is less than 10%, while the existing commercial nanofiltration membranes can remove antibiotic pollutants in water by 90%, but the membrane flux is low, usually less than 10L / (m 2 ·h·bar). Therefore, providing a separation membrane with excellent separation effect and good permeability for emerging antibiotic pollutants is a technical problem that needs to be solved urgently in the prior art. Summary of the invention
[0003] The purpose of the present invention is to provide a Zn / Co-MOFs / PVDF mixed matrix membrane and a preparation method and application thereof. The Zn / Co-MOFs / PVDF mixed matrix membrane prepared by the method provided by the present invention has good permeability, cooperates with advanced oxidation technology, can efficiently remove emerging antibiotic pollutants, and is green and environmentally friendly.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a Zn / Co-MOFs / PVDF mixed matrix membrane, comprising the following steps:
[0006] (1) mixing a zinc source, a cobalt source, terephthalic acid and a solvent, adding an alkali solution, and sequentially performing ultrasonic treatment and vacuum heating to obtain a Zn / Co-MOFs material;
[0007] (2) mixing the Zn / Co-MOFs material obtained in step (1) with polyvinyl pyrrolidone and an alcohol solvent, and performing a first ultrasonic stirring to obtain a modified Zn / Co-MOFs material;
[0008] (3) mixing the modified Zn / Co-MOFs material obtained in step (2) with dimethylacetamide, and performing a second ultrasonic stirring to obtain a first solution;
[0009] The first solution and polyvinyl pyrrolidone are mixed, and a third ultrasonic stirring is performed to obtain a second solution;
[0010] The second solution and polyvinylidene fluoride are mixed, and heated, stirred, cooled and degassed in sequence to obtain a degassed casting solution;
[0011] (4) The defoaming casting solution obtained in step (3) is sequentially subjected to scraping, pre-evaporation treatment, coagulation bath treatment, ultrapure water immersion and post-treatment to obtain a Zn / Co-MOFs / PVDF mixed matrix membrane.
[0012] Preferably, in step (1), the molar ratio of the zinc source, the cobalt source and the terephthalic acid is (0.5-2):(0.5-2):1.
[0013] Preferably, the temperature of the vacuum heating in step (1) is 90 to 110° C., and the time of the vacuum heating is 8 to 12 hours.
[0014] Preferably, in step (2), the mass ratio of Zn / Co-MOFs to polyvinyl pyrrolidone is (0.1-0.6):1.
[0015] Preferably, in step (3), the mass ratio of the modified Zn / Co-MOFs material, polyvinyl pyrrolidone and polyvinylidene fluoride is (0.1-0.5): (0.2-1.2): (34-45).
[0016] Preferably, the temperature of heating and stirring in step (3) is 60-80° C., and the time of heating and stirring is 6-10 h; and the degassing is performed at room temperature for 20-26 h.
[0017] Preferably, the temperature of the pre-evaporation treatment in step (4) is room temperature, and the time of the pre-evaporation treatment is 20 to 45 seconds.
[0018] Preferably, the post-treatment in step (4) comprises: washing and drying the pre-treated membrane obtained by soaking the ultrapure water in sequence to obtain a Zn / Co-MOFs / PVDF mixed matrix membrane.
[0019] The present invention also provides a Zn / Co-MOFs / PVDF mixed matrix membrane prepared by the preparation method described in the above technical solution.
[0020] The present invention also provides the use of the Zn / Co-MOFs / PVDF mixed matrix membrane described in the above technical solution in removing emerging antibiotic pollutants.
[0021] The present invention provides a Zn / Co-MOFs / PVDF mixed matrix membrane, which belongs to an organic-inorganic mixed matrix membrane. The present invention first prepares a two-dimensional Zn / Co-MOFs nanomaterial by a hydrothermal method, and then introduces Zn / Co-MOFs into a casting solution using PVDF as a raw material, PVP as a pore former, and DMAc as a solvent, and prepares a Zn / Co-MOFs / PVDF mixed matrix membrane by a non-solvent induced phase separation method (NIPS). The present invention introduces Zn / Co-MOFs materials into the mixed matrix membrane, realizes the successful coupling of advanced oxidation technology and membrane separation technology, and can not only solve the problems of difficult recovery of catalytic materials, need for carriers, reduced catalytic effect, and easy secondary pollution, but also can combine the separation function of the membrane, and finally effectively improve the removal ability of the mixed matrix membrane for small molecule pollutants such as tetracycline hydrochloride (TC). The present invention creatively develops a new membrane material for efficient removal of emerging antibiotic pollutants, which provides ideas for the development and construction of more new high-performance anti-pollution membrane materials. And from the perspective of improving the structure of the membrane material itself and developing coupling technology, the separation efficiency and service life of the membrane can be improved, ultimately achieving the practical goal of being green, environmentally friendly and reducing the cost of industrial wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The SEM and XRD diagrams of the Zn / Co-MOFs material prepared in Example 1 of the present invention are shown in FIG. Figure 1 (a) is the SEM image. Figure 1 (b) is the XRD pattern.
[0023] Figure 2 The surface SEM images and cross-sectional SEM images of the Zn / Co-MOFs / PVDF mixed matrix membrane prepared in Example 1 of the present invention and the pure PVDF membrane prepared in Comparative Example 1 are shown, wherein: Figure 2 (a) is the SEM image of the pure PVDF membrane surface. Figure 2 (b) is a surface SEM image of the Zn / Co-MOFs / PVDF mixed matrix membrane prepared in Example 1. Figure 2 (c) is a cross-sectional SEM image of pure PVDF membrane. Figure 2 (d) is a cross-sectional SEM image of the Zn / Co-MOFs / PVDF mixed matrix membrane prepared in Example 1;
[0024] Figure 3 The performance test results of M1, M2 and M3 prepared in Examples 1 to 3 of the present invention and M0 prepared in Comparative Example 1 are shown in FIG. Figure 3 (a) is the permeation flux of M1, M2, M3 and M0, Figure 3(b) shows the retention and removal rates of TC by M1, M2, M3 and M0. Figure 3 (c) shows the removal effect of M1, M2, M3 and M0 on TC. Figure 3 (d) shows the removal effect of different concentrations of PMS on TC, C T represents the current concentration, and C0 represents the initial concentration. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing a Zn / Co-MOFs / PVDF mixed matrix membrane, comprising the following steps:
[0026] (1) mixing a zinc source, a cobalt source, terephthalic acid and a solvent, adding an alkali solution, and sequentially performing ultrasonic treatment and vacuum heating to obtain a Zn / Co-MOFs material;
[0027] (2) mixing the Zn / Co-MOFs material obtained in step (1) with polyvinyl pyrrolidone and an alcohol solvent, and performing a first ultrasonic stirring to obtain a modified Zn / Co-MOFs material;
[0028] (3) mixing the modified Zn / Co-MOFs material obtained in step (2) with dimethylacetamide, and performing a second ultrasonic stirring to obtain a first solution;
[0029] The first solution and polyvinyl pyrrolidone are mixed, and a third ultrasonic stirring is performed to obtain a second solution;
[0030] The second solution and polyvinylidene fluoride are mixed, and heated, stirred, cooled and degassed in sequence to obtain a degassed casting solution;
[0031] (4) The defoaming casting solution obtained in step (3) is sequentially subjected to scraping, pre-evaporation treatment, coagulation bath treatment, ultrapure water immersion and post-treatment to obtain a Zn / Co-MOFs / PVDF mixed matrix membrane.
[0032] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0033] The invention mixes a zinc source, a cobalt source, terephthalic acid and a solvent, then adds an alkali solution, and sequentially performs ultrasonic treatment and vacuum heating to obtain a Zn / Co-MOFs material.
[0034] In the present invention, the zinc source is preferably at least one of zinc nitrate hexahydrate and zinc sulfate tetrahydrate. In the present invention, the cobalt source is preferably at least one of cobalt nitrate hexahydrate and cobalt chloride hexahydrate.
[0035] In the present invention, the molar ratio of the zinc source, the cobalt source and terephthalic acid is preferably (0.5-2): (0.5-2): 1, more preferably 1: 1: 1. The present invention controls the mass ratio of the zinc source, the cobalt source and terephthalic acid within the above range to improve the catalytic performance of the Zn / Co-MOFs material, improve the reaction efficiency, and thus improve the comprehensive performance of the Zn / Co-MOFs material. In the present invention, the solvent is preferably at least one of N, N-dimethylformamide and N-methyl-2-pyrrolidone.
[0036] In the present invention, the alkali solution is preferably a NaOH solution with a concentration of 0.4 mol / L.
[0037] In the present invention, the ultrasonic treatment is preferably carried out at room temperature and pressure for 20 to 40 minutes. The present invention uses ultrasonic treatment to help the reactants disperse more evenly and avoid agglomeration.
[0038] In the present invention, the temperature of the vacuum heating is preferably 90 to 110° C., more preferably 100° C., and the time of the vacuum heating is 8 to 12 hours. The present invention reduces the pressure in the reaction system through vacuum heating, promotes the diffusion of solutes, and thus improves the synthesis effect and purity of the prepared catalyst.
[0039] After the vacuum heating is completed, the present invention preferably sequentially performs a first centrifugation, washing, a second centrifugation and vacuum drying on the vacuum heated product to obtain a Zn / Co-MOFs material.
[0040] The present invention has no particular limitation on the first centrifugation and the second centrifugation, as long as solid-liquid separation is achieved. In the present invention, the washing is preferably performed in sequence with DMF and methanol twice each, each time for 3 hours.
[0041] In the present invention, the temperature of the vacuum drying condition is preferably 50-70° C., more preferably 60° C., and the vacuum drying time is preferably 10-14 h, more preferably 12 h. The present invention removes residual reagents by vacuum drying.
[0042] After obtaining the Zn / Co-MOFs material, the present invention mixes the Zn / Co-MOFs material with polyvinyl pyrrolidone and an alcohol solvent, and performs a first ultrasonic stirring to obtain a modified Zn / Co-MOFs material.
[0043] In the present invention, the mass ratio of Zn / Co-MOFs to polyvinyl pyrrolidone is preferably (0.1-0.6): 1, more preferably (0.2-0.4): 1. The present invention controls the mass ratio of Zn / Co-MOFs to polyvinyl pyrrolidone within the above range to ensure that polyvinyl pyrrolidone can effectively coat Zn / Co-MOFs at a suitable ratio, enhance its dispersibility and stability, and improve catalytic activity and reaction efficiency.
[0044] In the present invention, the alcohol solvent is preferably at least one of methanol and ethanol.
[0045] In the present invention, the first ultrasonic stirring is preferably ultrasonic stirring at room temperature and pressure for 20 to 26 hours. The present invention promotes uniform dispersion of reactants and enhances the interaction between substances through the first ultrasonic stirring, thereby improving reaction efficiency and reaction uniformity of materials.
[0046] After the first ultrasonic stirring is completed, the present invention sequentially washes and dries the product of the first ultrasonic stirring with methanol to obtain a modified Zn / Co-MOFs material.
[0047] In the present invention, the number of methanol washing is preferably 2 to 4 times. The present invention has no particular limitation on the drying method, as long as the residual reagent is removed.
[0048] After obtaining the modified Zn / Co-MOFs material, the present invention mixes the modified Zn / Co-MOFs material with dimethylacetamide, and performs a second ultrasonic stirring to obtain a first solution.
[0049] In the present invention, the mass ratio of the modified Zn / Co-MOFs material to dimethylacetamide is preferably (0.1-0.5): (10-20), and more preferably 0.3: 15.1. The present invention controls the mass ratio of the modified Zn / Co-MOFs material to dimethylacetamide within the above range to ensure uniform dispersion of the modified Zn / Co-MOFs material in dimethylacetamide, avoid incomplete dispersion of the material due to excessive solvent, and thus improve the catalytic efficiency and reaction rate.
[0050] In the present invention, the second ultrasonic stirring is preferably ultrasonic stirring at room temperature and pressure for 0.5 to 2 hours. The present invention uses the second ultrasonic stirring to ensure that dimethylacetamide as a solvent can form a uniform dispersion system with the Zn / Co-MOFs material.
[0051] After obtaining the first solution, the present invention mixes the first solution with polyvinyl pyrrolidone and performs a third ultrasonic stirring to obtain a second solution.
[0052] In the present invention, the third ultrasonic stirring is preferably ultrasonic stirring at room temperature and pressure for 0.5 to 2 hours. The present invention promotes the full mixing of polyvinyl pyrrolidone and other components in the first solution through the third ultrasonic stirring, ensures that the pore former is evenly dispersed in the solution, and thus forms a uniform pore structure in the membrane material.
[0053] After obtaining the second solution, the present invention mixes the second solution with polyvinylidene fluoride, and sequentially performs heating and stirring, cooling and degassing to obtain a degassing casting solution.
[0054] In the present invention, the mass ratio of the modified Zn / Co-MOFs material, polyvinyl pyrrolidone and polyvinylidene fluoride is preferably (0.1-0.5): (0.2-1.2): (34-45), and more preferably 0.3: 0.8: 38. The present invention controls the mass ratio of the three within the above range to ensure uniform dispersion of the catalyst while optimizing the efficiency of the catalytic reaction, thereby achieving the best pollutant removal effect.
[0055] In the present invention, the temperature of the heating and stirring is preferably 60 to 80°C, more preferably 70°C, and the time of the heating and stirring is preferably 6 to 10 hours, more preferably 8 hours. The present invention promotes uniform dispersion of components and avoids particle aggregation by heating and stirring, thereby improving the stability and uniformity of the casting liquid. In the present invention, the cooling is preferably natural cooling. In the present invention, the degassing is preferably room temperature degassing for 20 to 26 hours. The present invention removes bubbles in the casting liquid by degassing to avoid the generation of defects on the surface and inside of the membrane, thereby improving the density of the membrane.
[0056] After obtaining the degassing casting solution, the present invention sequentially performs scraping, pre-evaporation treatment, coagulation bath treatment, ultrapure water immersion and post-treatment on the degassing casting solution to obtain a Zn / Co-MOFs / PVDF mixed matrix membrane.
[0057] In the present invention, the scraping method is preferably to inject the defoaming casting solution onto the flat substrate, and then use a film applicator to scrape out a film of uniform size and thickness.
[0058] In the present invention, the temperature of the pre-evaporation treatment is preferably room temperature, and the time of the pre-evaporation treatment is preferably 20 to 45 seconds, more preferably 30 seconds.
[0059] In the present invention, the coagulation bath treatment is preferably to immerse the product after the pre-evaporation treatment horizontally in a deionized water coagulation bath for phase separation.
[0060] In the present invention, the ultrapure water immersion time is preferably 10 to 14 hours.
[0061] In the present invention, the post-treatment comprises: drying the pre-treated membrane obtained by soaking the ultrapure water to obtain a Zn / Co-MOFs / PVDF mixed matrix membrane.
[0062] In the present invention, the cleaning is preferably cleaning with deionized water. The present invention has no particular limitation on the drying method, as long as the water is removed.
[0063] The present invention also provides a Zn / Co-MOFs / PVDF mixed matrix membrane prepared by the preparation method described in the above technical solution.
[0064] The present invention also provides the use of the Zn / Co-MOFs / PVDF mixed matrix membrane described in the above technical solution in removing emerging antibiotic pollutants.
[0065] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] Example 1
[0067] A method for preparing a Zn / Co-MOFs / PVDF mixed matrix membrane comprises the following steps:
[0068] (1) At room temperature, 1.35 g (5 mmol) Zn(NO3)2·6H2O, 1.35 g (5 mmol) Co(NO3)2 and 0.83 g (5 mmol) BDC were weighed and dissolved in a beaker containing 50 mL DMF, and then 10 mL NaOH (0.4 mol / L) was added and ultrasonically treated for 30 min at room temperature and pressure. After the solid was completely dissolved, the precursor solution was poured into a 100 mL hydrothermal reactor and heated in a vacuum drying oven at 100 °C for 10 h. The solid product was obtained by the first centrifugation separation sample, and washed twice with DMF and methanol, each for 3 h, respectively, and then centrifuged for a second time. The obtained product was placed in a vacuum drying oven at 60 °C and dried for 12 h to obtain Zn / Co-MOFs material;
[0069] The molar ratio of zinc source Zn(NO3)2·6H2O, cobalt source Co(NO3)2 and terephthalic acid BDC is 1:1:1;
[0070] (2) Accurately weigh 1 g of PVP and 0.3 g of the Zn / Co-MOFs obtained in step (1), pour them into a reagent bottle containing 20 mL of methanol solvent, and stir them ultrasonically at room temperature and pressure for 24 h. The obtained product is washed three times with methanol and placed in a drying oven at 40° C. for 12 h to obtain a modified Zn / Co-MOFs material;
[0071] In the step (2), the mass ratio of Zn / Co-MOFs to polyvinyl pyrrolidone (PVP) is 0.3:1;
[0072] (3) Accurately weigh 0.3 g of the modified Zn / Co-MOFs material obtained in step (2), pour it into a reagent bottle containing 15.1 g of DMAc solvent, and stir it ultrasonically at room temperature and pressure for 1 h to obtain a first solution;
[0073] Accurately weigh 0.8 g of PVP and dissolve it in the first solution, and continue ultrasonic stirring for 30 min to mix evenly to obtain a second solution;
[0074] Accurately weigh 3.8 g of PVDF powder and dissolve it in the second solution, heat and stir at 70° C. for 8 h to fully dissolve it, to obtain a homogeneous casting solution, then naturally cool the casting solution, and degas at room temperature for 24 h to obtain a degassing casting solution;
[0075] In the step (3), the mass ratio of the modified Zn / Co-MOFs material, polyvinyl pyrrolidone (PVP) and polyvinylidene fluoride (PVDF) is 0.3:0.8:38;
[0076] (4) Take out the casting solution obtained in step (3) of complete degassing, pour it slowly on a clean flat glass, adjust the thickness of the applicator to 200 μm, scrape out a film of uniform size and thickness, pre-evaporate the film in the air for 30 seconds, immerse it horizontally in a coagulation bath (H2O) for 5 minutes to cause phase separation, and after it completely falls off the glass plate, take out the membrane material and replace it in another container containing ultrapure water to soak for 12 hours, and place the membrane material in a forced air drying oven to dry, thereby obtaining a Zn / Co-MOFs / PVDF mixed matrix membrane, referred to as M3.
[0077] Embodiment 2, 3
[0078] The Zn / Co-MOFs / PVDF mixed matrix membrane was prepared according to the method of Example 1. The difference from Example 1 is that the amounts of DMAc, PVP, PVDF and Zn / Co-MOFs in step (3) described in Examples 2 and 3 are different. The raw material contents of the Zn / Co-MOFs / PVDF mixed matrix membranes (referred to as M1 and M2) prepared in Examples 2 and 3 are specifically shown in Table 1.
[0079] Comparative Example 1
[0080] A pure PVDF membrane (abbreviated as M0) was prepared according to the method of Example 1. The difference from Example 1 is that the amounts of DMAc, PVP, PVDF and Zn / Co-MOFs in step (3) described in Example 1 are different. The specific contents of the raw materials are shown in Table 1.
[0081] Table 1 Composition of corresponding membranes prepared in Examples 1 to 3 and Comparative Examples
[0082]
[0083] The Zn / Co-MOFs were characterized by SEM, and the SEM and XRD patterns of the Zn / Co-MOFs material prepared in Example 1 of the present invention were obtained as shown in FIG. Figure 1 As shown, Figure 1 (a) is the SEM image. Figure 1 (b) is the XRD pattern. Figure 1 It can be seen that the Zn / Co-MOFs material prepared in Example 1 is an irregular flower ball-shaped two-dimensional nanostructure, and the surface contains many regular particle structures. 2+ The regulation of morphology provides the Zn / Co-MOFs material catalyst with abundant active sites and excellent specific surface area, which is beneficial to the degradation of pollutants in the MOFs / PMS system. As shown in the XRD spectrum of the Zn / Co-MOFs material ( Figure 1 (b)), all diffraction peaks match those of Zn-MOF and Co-MOF. With the decrease of the lattice constant and the contraction of the unit cell, the diffraction peaks move to wider angles, indicating that Example 1 successfully prepared Zn / Co-MOFs material.
[0084] The surface SEM images and cross-sectional SEM images of the Zn / Co-MOFs / PVDF mixed matrix membrane prepared in Example 1 and the pure PVDF membrane prepared in Comparative Example 1 are shown in FIG. Figure 2 As shown, Figure 2 (a) is the SEM image of the pure PVDF membrane surface. Figure 2 (b) is a surface SEM image of the Zn / Co-MOFs / PVDF mixed matrix membrane prepared in Example 1. Figure 2 (c) is a cross-sectional SEM image of pure PVDF membrane. Figure 2 (d) is a cross-sectional SEM image of the Zn / Co-MOFs / PVDF mixed matrix membrane prepared in Example 1. Figure 2It can be seen that the Zn / Co-MOFs material catalyst has good contact with the polymer matrix in the Zn / Co-MOFs / PVDF mixed matrix membrane prepared in Example 1, and the membrane is dense and defect-free. It can be observed from the SEM section of the membrane that all membranes have a dense skin layer and a finger-like support layer, which is a typical structure of NIPS membranes.
[0085] Performance Testing
[0086] The permeation flux and the retention rate of small molecule organic pollutants (tetracycline hydrochloride (TC)) of the Zn / Co-MOFs / PVDF mixed matrix membranes prepared in Examples 1 to 3 and the corresponding membranes prepared in Comparative Example 1 were tested at room temperature and pressure, respectively, as well as the removal rate of small molecule pollutants (TC) by the synergistic advanced oxidation technology (using PMS activated peroxymonosulfate), the steps are: the permeation is tested by a dead-end filtration device, first, the membrane is installed in the experimental equipment, and pre-pressed for 20 minutes to ensure the stability of the membrane performance, then, 100mL of deionized water is used for the filtration experiment, and the time of passing through the membrane is recorded, and then the permeability is calculated. The test steps of the retention rate are similar to the permeation test. The specific operation is to filter 100mL of tetracycline hydrochloride (TC) solution of known concentration through the pre-pressed membrane, collect the permeate after filtration, and measure the TC concentration in the permeate by UV-visible spectrophotometer, and calculate the retention rate of TC by the membrane by comparing the initial solution concentration and the permeate concentration; the removal rate test is carried out in a cross-flow device under full-cycle operation mode, first, the membrane is pre-pressed to ensure its stability and effective operation, and then a certain amount of permonosulfate (PMS) and TC mixed solution is used for testing, during the experiment, samples are taken from the system every 5 minutes, and the test is carried out for a total of 25 minutes, through this process, the change of TC concentration is monitored in real time, so as to evaluate the removal effect of the synergistic oxidation process on pollutants; during the experiment, the concentration of TC is measured by ultraviolet spectrophotometer (UV-Vis), among which C T represents the current concentration, and C0 represents the initial concentration. By comparing the concentration changes before and after treatment, the permeability of the membrane and the interception capacity of small molecular organic pollutants are evaluated. The performance results of M1, M2 and M3 prepared in Examples 1 to 3 and M0 prepared in Comparative Example 1 are shown in the figure below. Figure 3 As shown, Figure 3 (a) is the permeation flux of M1, M2, M3 and M0, Figure 3 (b) shows the retention and removal rates of TC by M1, M2, M3 and M0. Figure 3 (c) shows the removal effect of M1, M2, M3 and M0 on TC. Figure 3 (d) shows the removal effect of different concentrations of PMS on TC.
[0087] Depend on Figure 3 It can be seen that the permeation flux of pure PVDF polymer membrane is 85.82L / (m 2 ·h), the best permeation flux of M3 membrane is 130.28L / (m 2 h). According to Figure 3 As shown in (b), the retention rates of TC by membranes M0 to M3 were 10.05%, 17.66%, 20.31%, and 25.00%, respectively, which did not achieve the expected effect. The introduction of advanced oxidation technology effectively improved the removal capacity of different membranes for TC. Under visible light conditions, when the input amount of PMS was 1mM, the removal rates of TC by M0 to M3 were increased to 51.87%, 73.75%, 91.39%, and 99.37%, respectively (as shown in Figure 2). Figure 3 (c)). When the input amount of PMS was 0.5mM, 1mM, and 1.5mM, the removal rate of TC by M3 was 73.91%, 99.13%, and 91.42%, respectively. Figure 3 (d) shows that when the input amount of PMS is 1mM, the membrane has the best removal effect on TC. Combining membrane separation technology with advanced oxidation technology can not only solve the problems of difficult recovery and reuse of catalytic materials, the need for carriers, reduced catalytic effect and easy secondary pollution, but also give full play to the separation ability of the membrane and use the mixed matrix membrane directly to remove small molecular pollutants.
[0088] In summary, the present invention uses a non-solvent induced phase separation method to modify the Zn / Co-MOFs material for the membrane, thereby improving the separation effect of the prepared Zn / Co-MOFs / PVDF mixed matrix membrane. At the same time, the Zn / Co-MOFs / PVDF mixed matrix membrane separation technology is combined with the advanced oxidation technology to achieve an efficient removal effect on small molecule organic pollutants such as antibiotics. The present invention improves the membrane surface and internal structure through the modification of Zn / Co-MOFs. The high performance is mainly manifested in: (1) The permeation flux is 85.82L / (m 2 Compared with the M3 membrane, the permeation flux increased to an optimal 130.28 L / (m 2·h) (at this time, the Zn / Co-MOFs content is 1.5%), which is increased by 51.8%; (2) The retention rate of the antibiotic tetracycline hydrochloride (TC) by the M3 membrane is increased from 10.05% of the pure PVDF polymer membrane to the optimal 25.00% (at this time, the Zn / Co-MOFs content is 1.5%). As the content of Zn / Co-MOFs material in the Zn / Co-MOFs / PVDF mixed matrix membrane prepared by the present invention increases, the separation effect of the membrane is greatly improved, the permeability is also improved, and the flux and retention are improved at the same time, which breaks the trade-off effect in the membrane field to a certain extent. Therefore, the modification scheme provided by the present invention enhances the comprehensive performance of the membrane and provides a certain reference value for the development of new membrane materials.
[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Zn / Co-MOFs / PVDF mixed matrix membrane, characterized in that: The following steps are involved: (1) mixing a zinc source, a cobalt source, terephthalic acid and a solvent, adding an alkali solution, and sequentially performing ultrasonic treatment and vacuum heating to obtain a Zn / Co-MOFs material; (2) mixing the Zn / Co-MOFs material obtained in step (1) with polyvinyl pyrrolidone and an alcohol solvent, and performing a first ultrasonic stirring to obtain a modified Zn / Co-MOFs material; (3) mixing the modified Zn / Co-MOFs material obtained in step (2) with dimethylacetamide, and performing a second ultrasonic stirring to obtain a first solution; The first solution and polyvinyl pyrrolidone are mixed, and a third ultrasonic stirring is performed to obtain a second solution; The second solution and polyvinylidene fluoride are mixed, and heated, stirred, cooled and degassed in sequence to obtain a degassed casting solution; (4) The defoaming casting solution obtained in step (3) is sequentially subjected to scraping, pre-evaporation treatment, coagulation bath treatment, ultrapure water immersion and post-treatment to obtain a Zn / Co-MOFs / PVDF mixed matrix membrane.
2. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of the zinc source, the cobalt source and the terephthalic acid is (0.5-2):(0.5-2):
1.
3. The preparation method according to claim 1, characterized in that: The temperature of the vacuum heating in the step (1) is 90 to 110° C., and the time of the vacuum heating is 8 to 12 hours.
4. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of Zn / Co-MOFs to polyvinyl pyrrolidone is (0.1-0.6):
1.
5. The preparation method according to claim 1, characterized in that: In the step (3), the mass ratio of the modified Zn / Co-MOFs material, polyvinyl pyrrolidone and polyvinylidene fluoride is (0.1-0.5): (0.2-1.2): (34-45).
6. The preparation method according to claim 1, characterized in that: The heating and stirring temperature in the step (3) is 60 to 80° C., and the heating and stirring time is 6 to 10 hours; the degassing is performed at room temperature for 20 to 26 hours.
7. The preparation method according to claim 1, characterized in that: The temperature of the pre-evaporation treatment in the step (4) is room temperature, and the time of the pre-evaporation treatment is 20 to 45 seconds.
8. The preparation method according to claim 1, characterized in that: The post-treatment in step (4) includes: washing and drying the pre-treated membrane obtained by immersing the ultrapure water in sequence to obtain a Zn / Co-MOFs / PVDF mixed matrix membrane.
9. A Zn / Co-MOFs / PVDF mixed matrix membrane prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the Zn / Co-MOFs / PVDF mixed matrix membrane according to claim 9 in removing emerging antibiotic pollutants.
Citation Information
Cited By
Preparation method and application of functional catalytic membrane for sewage treatment
CN121446501A